Shipwreck in Seal Bay - Marlin, Jen (Marlin, Jen. Wind riders, 2022)
Mayday, Mayday! A rough storm has caused a boat to break loose and run aground on the rocks. Black, greasy oil is leaking from it's engine fast. And there are very curious harbor seals in the area, along with other wildlife! This disaster is what Sofia and Max find when their magical boat, Wind Rider, drops them off at Scotland's beautiful craggy coastline for their latest mission. These two friend must figure out a way to quickly contain the spill before it can harm any harbor seals.